Egypt : a short history - Tignor, Robert L. (Princeton University Press, 2011)
This is a sweeping, colorful, and concise narrative history of Egypt from the beginning of human settlement in the Nile River valley 5000 years ago to the present day. Accessible, authoritative, and richly illustrated, this is an ideal introduction and guide to Egypt's long, brilliant, and complex history for general readers, tourists, and anyone else who wants a better understanding of this vibrant and fascinating country, one that has played a central role in world history for millennia--and that continues to do so today. Respected historian Robert Tignor, who has lived in Egypt at different.